CLARYTROMYCIN IN TREATMENT OF PEDIATRIC ACUTE RESPIRATORY DISEASES - A. Yu. Simonova ("Paediatrician" Publishers LLC, 2012)
Acute respiratory diseases still occupy leading positions among all pediatric diseases. This article contains modern data upon etiology of acute and recurrent bronchitides, as well as that of out-of-hospital pneumonias in children. Special attention is paid to the choice of antibacterial therapy. We observe modern Russian and international data upon bacterial resistance to antibacterial drugs. This article also contains description of biological, pharmacokinetic and antibacterial traits of macrolides, especially these of clarytromycin with description of its use in treatment of pediatric respiratory disorders.